Scaling laws for ring-shaped beam profiles in laser-based powder bed fusion of metals - Jonas Grünewald; Moritz Wittemer; Katrin Wudy (Advances in Industrial and Manufacturing Engineering)
The application of alternative beam shapes is a current research trend to stabilize and accelerate the laser-based powder bed fusion of metals process. Although many publications show a reduced process dynamic and an enlargement of the process window for dense components using non-Gaussian beam profiles, a generally valid correlation between the energy input - in terms of the beam shape and the process parameters - and the melting mode is lacking. Consequently, intensive experimental work is required to qualify process parameters for alternative beam profiles. The present work aims to reduce this experimental effort for the parameter qualification of alternative beam profiles by estimating the melting modes based on dimensionless parameters. For this purpose, a simple heat conduction model is applied to a new database of melt track widths and depths generated with various ring-shaped beam profiles with different spot sizes. The approach shows a correlation between the dimensionless enthalpy and the melt track depth and width if the 2nd moment method is used to determine the spot size of the laser beam profiles. Finally, introducing a maximum dimensionless enthalpy considering the peak intensity of the beam profile used enables the estimation of the melting mode. Regardless of the beam profile, the transition from conduction mode to keyhole mode occurs between maximum dimensionless enthalpies of 6.25 ± 0.85 and 8.65 ± 0.30.